Optimizing APBD Budget Administration and Expenditure Accountability for Strengthened Accountable Regional Financial Governance in Jayawijaya Regency - Lukas Wenda; Arius Kambu; Maylen K. P. Kambuaya; Agustinus Salle; Westim Ratang; Juliana Waromi (Manunggal Halim Jaya, 2026)
Accountable regional financial management is a fundamental prerequisite for achieving good governance, particularly in regions with limited infrastructure and institutional capacity such as Jayawijaya Regency. Although regulations and information systems have been established, the practices of budget administration and expenditure accountability still face various challenges that potentially hinder the effectiveness of budget management. This study aims to analyze the actual condition of budget administration and expenditure accountability of the Regional Revenue and Expenditure Budget (APBD), identify the constraints encountered, and formulate optimization strategies for regional financial management in Jayawijaya Regency. This research employs a qualitative approach with a descriptive research design. Data were obtained from informants selected through purposive sampling, consisting of officials and technical staff from the Regional Financial and Asset Management Agency, the Inspectorate, and related Regional Apparatus Organizations in Jayawijaya Regency. The results indicate that budget administration and expenditure accountability have not been optimally implemented, as reflected in administrative delays, inconsistencies in documentation, and uneven utilization of financial information systems. The main constraints include limited human resource capacity, weak inter-unit coordination, and differing interpretations of regulations. The implications of this study highlight the importance of strengthening personnel capacity, standardizing procedures, optimizing information systems, and enhancing the role of internal supervision and leadership in promoting more transparent and accountable regional financial governance.